Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1016/j.fuel.2013.04.026
|View full text |Cite
|
Sign up to set email alerts
|

An experimental study of ash behaviour and the potential fate of ZnO/Zn in the Co-combustion of pulverised South African coal and waste tyre rubber

Abstract: A Novel combustion application utilising waste tyre rubber (WTR) as a secondary fuel in pulverised coal power plants is presented. Co-combustion of a South African coal (SAf) with WTR at the fuel fractions (FF) 4.1%, 14.1% and 19.7% along with the pure firing of WTR was conducted in an 80 kWth combustion test facility (CTF). This study assessed the potential slagging and fouling behaviour of the resultant ashes produced from co-firing SAf/WTR and pure fired WTR. XRF and ICP/OES analysis of the co-fired SAf/WTR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 41 publications
(71 reference statements)
0
8
0
Order By: Relevance
“…In addition to the cofiring of coal and sludge, few researchers explored the slagging/fouling behavior during the co-combustion of coal and other OSWs. For example, Singh et al peerformed the co-combustion experiments of a South African coal with waste tire rubber in an 80 kWth combustion test facility. The results indicated that the co-combustion ashes had a low risk of slagging/fouling and ZnO would not contribute to in-furnace slagging, showing the potential use of waste tire rubber as a secondary fuel within coal-fired boilers.…”
Section: Ash-related Issues During Co-combustion Of Osw and Coalmentioning
confidence: 99%
“…In addition to the cofiring of coal and sludge, few researchers explored the slagging/fouling behavior during the co-combustion of coal and other OSWs. For example, Singh et al peerformed the co-combustion experiments of a South African coal with waste tire rubber in an 80 kWth combustion test facility. The results indicated that the co-combustion ashes had a low risk of slagging/fouling and ZnO would not contribute to in-furnace slagging, showing the potential use of waste tire rubber as a secondary fuel within coal-fired boilers.…”
Section: Ash-related Issues During Co-combustion Of Osw and Coalmentioning
confidence: 99%
“…A reduction of ash loops reduced the amount of potassium transferred from the combustion reactor to the gasication reactor. Singh et al 175 assessed the potential slagging and fouling behaviour of the ash produced from cocombustion of a South African coal with waste tyre rubber (WTR) along with pure red WTR. Zinc oxide is incorporated during the manufacture of tyres as a compounding additive and was also present within raw WTR.…”
Section: Industrial Materials and Consequences Of Industrial Activitymentioning
confidence: 99%
“…This liquid phase, slag-melt, might cause serious ash deposition problems. Meanwhile, alkali earth and alkali metals (K, Mg, Ca and Na) are likely to condense on the cooler zones of the boiler [30]. The total content of SiO 2 and Al 2 O 3 decreased with an increase in sewage sludge content, indicating that the ash generated from co-combustion would weaken hydration activity when used in the preparation of cementious materials.…”
Section: Influencing Factors Of Slagging Characteristicsmentioning
confidence: 99%